Inequality of Outcomes vs. Inequality of Opportunities in a Developing Country. An exploratory analysis for Chile - Nuñez, Javier (Estudios de Economía, 2016)
We apply a variation of Bourguignon, Meléndez and Ferreira (2005) methodology to examine the extent to which income inequality is associated with the inequality of observed exogenous circumstances of origin that determine individuals’ “opportunities” to pursue their chosen life plans. We find that equalizing a set of observed circumstances of origin across individuals such as parents’ schooling, parents’s stability of employment, father’s age, household size and growing in a single vs a bi-parental household reduces income inequality, but in a small margin, in the range of 8 to 13 points of the Gini coefficient, about a 15-20 per cent drop. These results are similar to those obtained by Bourguignon et al. (2005) for Brazil, although the dataset and the set of observed circumstances are partially different. These results suggest that a significant part of income inequality may be associated with unobserved heterogeneity across individuals unrelated to circumstances of origin, such as preferences, effort and sheer luck, transitory shocks and measurement errors in income. However, assessing the relative importance of these factors vs. the role of unobserved circumstances remains as future research.